Synthesizing a Planar Four Bar Linkage and Coupler Curve - James, V.; Sivakumar, B. (Communications in Mathematics and Applications, 2021)
Synthesis of planar four bar mechanism is an important area in robotics and mechanical engineering. The analysis of the lengths of the four-bar mechanism and the associated angle helps in determining the coupler curve. In this paper, we present the problem of synthesizing a planar four-bar linkages whose coupler curve passes through five precision points that points are chosen from quadratic polynomial function. Also, we analyze its solution and to find out suitable solution for a chosen coupler curve.